Aircraft measurements of black carbon vertical profiles show upper tropospheric variability and stability. Issue 2 (26th January 2017) - Schwarz, Joshua P.; Weinzierl, Bernadett; Samset, Bjørn H.; Dollner, Maximilian; Heimerl, Katharina; Markovic, Milos Z.; Perring, Anne E.; Ziemba, Luke
Abstract: We present new data sets of black carbon (BC) aerosol mass mixing ratio (MMR) obtained from aircraft missions over North America, Europe, the Arctic, and the outflow region of Saharan Africa before and after trans‐Atlantic transport. The data, collected from 2011 to 2013 with single‐particle soot photometers, provide new insight into the variability and distribution of BC over global scales and refine understanding of AeroCom global model ensemble performance. The results indicate extensive global‐scale longitudinal mixing of BC above altitude pressures as low as 400 hPa. They also constrain the absolute and temporal variability of upper tropospheric BC MMR and point to opportunities for new tests of global aerosol models in the upper troposphere. A comparison to the AeroCom Phase II results generally reinforces previous estimates of the ensemble performance, except that it also strengthens confidence that the ensemble actually is biased high in the Arctic in all seasons. Key Points: A new large data set of black carbon aerosol vertical profiles has been collected and analyzed with comparison to global models AeroCom global models do not underestimate Arctic BC loads Upper tropospheric BC loadings provide a powerful constraint on model transport and removal processes